الأذية الكلوية الحادة المكتسبة في المشفى:الأسباب والعقابيل دراسة عينة من مرضى مشفى الأسد الجامعي - لايقة, عنان (Latakia University Journal -Medical Sciences Series, 2019)
أصبحت الأذية الكلوية الحادة أكثر شيوعاً إذ تحدث بشكل متزايد عند مرضى المشافي البالغين. لقد قمنا بدراسة مستقبلية لتحديد أسباب وعقابيل الأذية الكلوية الحادة المكتسبة في مشفى الأسد الجامعي – سورية خلال سنة كاملة, شملت هذه الدراسة المرضى الذين أظهروا ارتفاعاً حاداً في كرياتينين المصل أثناء قبولهم في المشفى، وقد حصلنا على المعطيات السريرية لكل مريض من سجلات المرضى. (تشمل عقابيل الأذية الكلوية الحادة الحاجة للعلاج بالتنقية الدموية, مدة البقاء في المشفى, والوفيات داخل المشفى). شملت هذه الدراسة 124 مريضاً من المرضى المقبولين في المشفى, متوسط أعمارهم 59 سنة. وقد كانت الأسباب الأكثر شيوعاً للأذية الكلوية الحادة عند هؤلاء المرضى كالتالي: إنتان الدم (31% ) من المرضى, السمية المتعلقة بالدواء (22%), نقص التروية الكلوية المتعلقة بالتجفاف وانخفاض التوتر الشرياني وقصور القلب (13%)، المادة الظليلة (10%) والجراحة (6,5 %) كما بلغ معدل وفيات المرضى داخل المشفى 30%. Acute kidney injury (AKI) is becoming increasingly common in elderly individuals. We undertook a prospective study to define the causes and outcome ( renal replacement therapy requirement, length of hospital stay, and in-Hospital mortality), of hospital acquired acute renal failure in al-Assad university Hospital-Syria. Over a year period, patients who developed acute elevation in serum creatinine during the hospital stay were studied, Clinical outcomes were obtained from each patient's case records. In hospitalized patients,.124 patients , satisfied the criteria for entering into the study. Median age was 59 yr for AKI .The most frequent causes of AKI in hospitalized patients are: Sepsis was a precipitating factor in 31% of patients, medication-related toxicity (22 %), decreased perfusion related to dehydration, hypotension or cardiac insufficiency(13%), radiocontrast-related(10%)and surgery (6,5%).with in-Hospital mortality rate of 30%.